Focolare As An Instrument for Unity Toward A Cohesive Society in IndonesiaA - Oktaviyanti, Sri Safitri; Laksana, Albertus Bagus; Sofjan, Dicky (Journal of Asian Orientation in Theology, 2025)
The research focuses on social cohesive elements in the Focolare movement in Indonesia which attribute unity to their surroundings. Inclusion, a sense of belonging, recognition, and active participation create bonds among its members and sympathisers. The Focolare movement attracts those who strive to minimise every division to achieve its goal “may all be one” by collectively living the spirituality of unity despite their varied identities and experiences. This research seeks to understand the definition of unity which puts Focolare as one family. It aims to recognise how members’ engagement and participation enhance mutual understanding, empathy, and respect, to create unity. This unity is seen as a social cohesion in the society, within and outside the movement. The case study is conducted on a qualitative approach using semi-structured interviews, with people of three religions who practise Focolare spirituality in their daily lives in Indonesia. The research finds several relational paths which help the creation of unity in Focolare, resulting as instruments for unity. The paths take form in three cohesive elements; social relations, identification, and participation toward common goods. The acknowledgement of other religious traditions and the reflection on seeing the world as one family enable the acceptance of shared values. Those who are willing to work toward unity underline the importance of inclusion, the sense of one family, recognition of differences at open forums, and concrete programs of formation in and among religious communities. It later encourages the intercultural and interreligious relation toward cohesion in the society of diverse Indonesia.